Temperature-controlled radiofrequency ablation of different tissues using two-compartment models. (17th February 2017) - Singh, Sundeep; Repaka, Ramjee
Abstract: Purpose: This study aims to analyse the efficacy of temperature-controlled radiofrequency ablation (RFA) in different tissues. Materials and methods: A three-dimensional, 12 cm cubical model representing the healthy tissue has been studied in which spherical tumour of 2.5 cm has been embedded. Different body sites considered in the study are liver, kidney, lung and breast. The thermo-electric analysis has been performed to estimate the temperature distribution and ablation volume. A programmable temperature-controlled RFA has been employed by incorporating the closed-loop feedback PID controller. The model fidelity and integrity have been evaluated by comparing the numerical results with the experimental in vitro results obtained during RFA of polyacrylamide tissue-mimicking phantom gel. Results: The results revealed that significant variations persist among the input voltage requirements and the temperature distributions within different tissues of interest. The highest ablation volume has been produced in hypovascular lungs whereas least ablation volume has been produced in kidney being a highly perfused tissue. The variation in optimal treatment time for complete necrosis of tumour along with quantification of damage to the surrounding healthy tissue has also been reported. Conclusions: The results show that the surrounding tissue environment significantly affects the ablation volume produced during RFA. The optimal treatment time for complete tumour ablation can play a critical role in minimising the damage to the surrounding healthy tissue and ensuring safe and risk free application of RFA. The obtained results emphasise the need for developing organ-specific clinical protocols and systems during RFA of tumour.